Implementation of Disciplinary Character Education: A Comparative Study of Indonesia and New Zealand Primary Schools - Muthmainah, Lulu Hanifah; Hidayat, Muhamad Taufik (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This research compares disciplinary character education in Indonesian and New Zealand elementary schools. Method: The method used in this research is descriptive qualitative with a literature review study design; the type of research is a comparative literature review. The data obtained from this research is secondary data. Data collection techniques use listening techniques and note-taking techniques. Data validity uses check and recheck methods, researcher validity, and source triangulation. The data analysis used is (1) data reduction, (2) data presentation, and (3) data conclusions. Result: The results of this research show that, in implementing character education in elementary schools in Indonesia and New Zealand, there are several similarities in rules, punishments, and rewards. (1) The purpose of having rulesau in schools is to improve student discipline, (2) punishment for students who violate discipline in Indonesian and New Zealand schools both receive punishment, namely students are given a warning, request sorry, and getting extra assignments, (3) awards for students who have applied discipline in Indonesian and New Zealand elementary schools. Students get extra points and appreciation by saying